1982
DOI: 10.1017/s0033291700043385
|View full text |Cite
|
Sign up to set email alerts
|

Early improvement as a predictor of response to amitriptyline and nortriptyline: a comparison of 2 patient samples

Abstract: SynopsisThis study compared serial severity ratings from 2 methodologically similar tricyclic antidepressant studies. Though the groups resembled each other in terms of diagnosis and baseline severity, response patterns were surprisingly different. In particular, early change was highly predictive of outcome in one group but not in the other. The results of response predictor studies must, therefore, be generalized with caution. These data, nevertheless, do allow some guidelines for predicting response from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…A recent study [5] reported the usefulness of the improve ment after the first week as a predictor of the final response to antidepressant treatment. These findings con firmed previous reports by Coryell et al [6], indicating that the first-two-weeks improvement rate is predictive of the treatment outcome.…”
Section: Introductionsupporting
confidence: 91%
“…A recent study [5] reported the usefulness of the improve ment after the first week as a predictor of the final response to antidepressant treatment. These findings con firmed previous reports by Coryell et al [6], indicating that the first-two-weeks improvement rate is predictive of the treatment outcome.…”
Section: Introductionsupporting
confidence: 91%
“…In our earlier study (Katz et al, 1987), the clinical effects detected within the first 2 weeks were large and were predictive of eventual positive clinical outcome. Findings from a number of other studies (Small et al, 1981;Coryell et al, 1982;Khan et al, 1989;Nagayama et al, 1991;Stassen et al, 1993;Boyer and Feighner, 1994) have also confirmed the positive role of early clinical actions in predicting treatment outcome. The capacity to predict outcome early in treatment would not only shorten the length of a treatment trial but should also decrease morbidity and the risk of suicide from prolonged depressive symptoms (Kiloh et al, 1988).…”
Section: Introductionmentioning
confidence: 58%
“…There have been, however, a number of studies over the years (Small et al, 1981;Coryell et al, 1982;Katz et al, 1987;Khan et al, 1989;Nagayama et al, 1991;Boyer and Feighner, 1994) that have demonstrated a relationship between early response to ADs, mainly tricyclics, and treatment outcome. It is clear from the current study, however, that drug-specific types of behavioral responses in the first 1 or 2 weeks of treatment with DMI or paroxetine are highly predictive of later outcome.…”
Section: Prediction Of Drug Responsementioning
confidence: 99%
“…In contrast, survival-analytical methods suggest that among responders, onset of action occurs in more than 70% of cases within the first two weeks of treatment, with an early onset of action being highly predictive of later response. (Angst and Stassen, personal communication;Stassen et al 1993Stassen et al , 1997Coryell et al 1982;Boyer and Feighner 1994).…”
Section: Onset and Speed Of Action Of Antidepressantsmentioning
confidence: 99%